A programmable, fast-fixing, osteo-regenerative, biomechanically robust bone screw. (February 2020) - Zhang, Yuanchi; Hu, Jinlian; Xie, Ruiqi; Yang, Yuhe; Cao, Jie; Tu, Yunhu; Zhang, Yi; Qin, Tingwu; Zhao, Xin
Abstract: The use of a screw for repairing defected bones is limited by the dilemma between stiffness, bioactivity and internal fixation ability in current products. For polymer bone screw, it is difficult to achieve the bone stiffness and osteo-induction. Polymer composites may enhance bioactivity and mechanical properties but sacrifice the shape memory properties enormously. Herein, we fabricated a programmable bone screw which is composed of shape memory polyurethane, hydroxyapatite and arginylglycylaspartic acid to resolve the above problem. This composite has significantly improved mechanical and shape-memory properties with a modulus of 250 MPa, a shape fixity ratio of ~90% and a shape recovery ratio of ~96%. Moreover, shape fixity and recovery ratios of the produced SMPC screw in the simulative biological condition were respectively ~80% and ~82%. The produced screw could quickly recover to its original shape in vitro within 20 s leading to easy internal fixation. Additionally, the composite could support mesenchymal stem cell survival, proliferation and osteogenic differentiation in vitro tests. It also promoted tissue growth and showed beneficial mechanical compatibility after implantation into a rabbit femoral intracondyle for 12 weeks with little inflammation. Such bone screw exhibited a fast-fixing, tightened fitting, enhanced supporting and boosted bioactivity simultaneously in the defective bone, which provides a solution to the long-standing problem for bone repairing. We envision that our composite material will provide valuable insights into the development of a new generation of bone screws with good fixation and osteogenic properties. Statement of Significance: The main obstacles to a wider use of a bone screw are unsatisfied stiffness, inflammatory response and screw loosening issues. Herein, we report a programmable screw with mechanically robust, bioactive and fast-fixing performances. The shape memory polymer composite takes advantage of the component in the natural bone and possesses a stable bush-like structure inside through the covalent bonding, and thus achieve significantly improved mechanical and memory properties. Based on its shape memory effect, the produced screw was proved to offer a recovery force to surroundings and promote the bone regeneration effectively. Therefore, the composite realizes our expectations on functions through structure design and paves a practical and effective way for the development of a new generation of bone screws. Graphical abstract: Image, graphical abstract